Carpal Tunnel Syndrome Complaints in Female Packing Workers - Nandini, Rizka Faliria; Lestari, Mona; Novrikasari, Novrikasari; Andarini, Desheila; Camelia, Anita; Fujianti, Poppy (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
The estimated prevalence of Carpal Tunnel Syndrome (CTS) in the general population is 1-5%. CTS can be experienced by workers who use hand strength at work. PT. X is one company that still uses manual labor in the process of packing soap and vermicelli. The purpose of this study was to determine the correlation between repetitive movements, wrist posture, age, history of illness, Body Mass Index (BMI), and years of service on CTS complaints. The research method used a cross-sectional study with a sample of 65 workers. Univariate, bivariate, and multivariate data analyses were using the chi-square and binary logistic regression test. Analysis of CTS complaints using a questionnaire and Phalen’s test. The results showed that as many as 40 workers (61.5%) experienced complaints of CTS. The results of statistical tests showed that the variable BMI was the most influential factor for the complaints of CTS (p = 0.031). In addition, workers who experience CTS complaints can also be influenced by repetitive movement (p = 0.024), age (p = 0.022), and years of service (p = 0.024). To prevent the severity and relieve complaints of CTS, packing workers can do stretching, massage, independent acupressure massage, and maintain a healthy lifestyle.